Simulation of Microwave Effects on Heating Some Bio-Oil Basic Components - Trimawiasa, Wayan; Sudiana, I Nyoman; Aba, La (BULETIN FISIKA, 2021)
An investigation of the microwave effect has been carried out by simulating heating the basic components of bio oil. This research aims to produce a heating model and energy distribution of oleic acid and stearic acid component materials. The cylindrical material is placed in a cavity-shaped heating applicator using a microwave excitation frequency of 2.45 GHz through a single waveguide TE 10 mode. Numerical solution using time-domain solver and transient solver succeeded in simulating the heating model of the dielectric material with the results of the energy distribution depending on the complex permittivity of the material.